Green economy post COVID-19: insights from Indonesia. Issue 1 (2nd January 2022) - Martawardaya, Berly; Rakatama, Ari; Junifta, Dhenny Yuartha; Maharani, Dinda Ayu
ABSTRACT: The COVID-19 pandemic has triggered a global economic crisis, including in Indonesia, demonstrating the vulnerability of the country's economic structure. However, the crisis may offer an opportunity to "build back better" and transition to a greener economy. Using qualitative data analysis, this study aims to analyse contemporary issues on green economy implementation in Indonesia. The authors found that transitioning to a green economy has been included in the national constitution and the 2020–2024 development plan. However, the economic recovery program does little to address environmental issues, demonstrating a lack of consistency between planning and implementation despite the pandemic. The country's economy still heavily depends on extractive sectors and primary commodities that negatively affect the environment. The opportunity to strengthen the green economy, which included the infusion of a sizeable government stimulus, was not fully utilised. This study suggests several policy options to promote green-economy transition including attracting green investment to Indonesia, switching from primary to secondary and tertiary commodities, suspending incentives for the extractive sectors and coal-fired power plants, and maintaining policy and regulation consistency related to the green economy.